Incorporation of private collections: a study on acquisition policies for State Archives in Brazil and Spain - Troitiño, Sonia [UNESP]; Colombo, Ana Beatriz [UNESP] (My University, 2022)
Nowadays, private records are considered important sources for research and for the preservation of memory, becoming the object of interest of public archives, when considering the expansion of their collections. Thus, it is necessary to discuss and improve the systems by which these additions are made, in order to make these acquisition processes representative and rationalized. As a resource to achieve these goals, the adoption of a collection acquisition policy brings transparency and normalization to the processes of incorporation of private documents to public institutions. In this sense, this paper seeks to discuss the process and rules of document acquisition by national archives, based on the study of two specific cases: the Brazilian Nacional Archives and the State Archives of Spain. For the development of this study, we divided the research into three parts: (1) theoretical survey; (2) data collection from the institutions object of the study; (3) data analysis. As a result, we were able to identify that acquisition policies are an important tool to regulate the incorporation of private records by state public archives, however, these procedures still need to be improved.
Incorporação de acervos privados: estudo sobre políticas de aquisição de arquivos estatais do Brasil e da Espanha
Keywords: Acquisition policies; Brazil; Private records; Public archives; Spain